Analisis Efisiensi Birokrasi dalam Administrasi Publik: Tinjauan Terhadap Proses Pengambilan Keputusan - Din El Hakim Malik; Aji Nurmanto; Jeihan Mahendra Putra; Adha Agung Saputro (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Bureaucratic efficiency is a key factor in ensuring the delivery of quality public services that are responsive to community needs. The decision-making process has a strategic role in implementing government policies and managing public resources. Best practices from other countries, such as the application of integrated information technology, simplification of administrative procedures, and active involvement of the community, serve as inspiration in developing corrective measures. The implications of this research are the importance of structural reforms, investment in information technology, changes in organizational culture, and increasing community involvement in decision-making processes as steps to improve bureaucratic efficiency in public administration.